The healing power of erotic dreams in the age of humanism - Molnár, Dávid (Primerjalna književnost, 2018)
The article explores the perception of erotic dreams in the works of fifteenth to seventeenth century humanists. Erotic dreams were undoubtedly a delicate theme, which humanists attempted to treat scientifically, to naturalize them, chiefly in medical works. The appearance of erotic dreams (most often dreams about sexual acts) was supposed to indicate the imbalance of humor in the human body. In other words, humanists argued that they not be signs of the devil's work, tempting people to sin, but a symptom of a diagnosable and curable physiological process. Moreover, erotic dreams did not merely help in diagnosing the imbalance of humors but could also have healing power because they could restore the appropriate proportion of the bodily fluids. Through antique, medieval and fifteenth- to seventeenth-century medical treatises, the article outlines how erotic dreams were interpreted in history, connected as much to spirituality as to bodily and mental diseases - especially to melancholy - and to love frenzy.
Keywords: antika; erotične sanje; fiziološka interpretacija; humanizem; manija; medicinske razprave; melanholija; srednji vek